T-forbidden excitation of isobaric analogue states in the 37Cl(p, α0)34S reaction - Bosnjakovic, B.; Leun, C. van der (Elsevier, 1966)
The analogues of the two lowest levels of 38Cl, with Jπ=3- and 5-, were excited in the T-forbidden reaction 37Cl(p, αo)34S. The Jπ=3- analogue state is split into several components which form a micro-giant resonance.
T-forbidden excitation of isobaric analogue states in the 37Cl(p, α0)34S reaction
Keywords: Natuur- en Sterrenkunde